UJI STABILITAS FISIK SEDIAAN SERUM WAJAH EKSTRAK DAUN BELIMBING MANIS (Averrhoa carambola L.) DENGAN VARIASI KONSENTRASI PROPILEN GLIKOL SEBAGAI HUMEKTAN - Devi Kurnia Saputri; Gigih Kenanga Sari; Estuningtyas Ayu Hapsari (Joseph: Journal of Science and Pharmacy, 2024)
Background: Sweet star fruit leaf (Averrhoa carambola L.) is a plant that contains antibacterial compounds such as alkaloids, flavonoids, saponins, tannins and triterpenoids that are used as acne therapy. Several product dosage forms have been developed for serum, one of which is in form slightly viscous. Humectants serve to improve the stability of the material over long period of time. Purpose: This research was conducted to find out at what oncentration propylene glycol as a humectant meets the physical stability test of a good serum preparations. Method: Sweet star fruit leaf (Averrhoa carambola L.) was extracted using the maceration method using methanol. The serum preparation consists of 3 formula with different concentrations of propylene glycol, namely formula I 15%, formula II 20% and formula III 25%. Evaluation of physical stability was carried out with 12 days in an accelerated test (Cycling test) with organoleptic testing parameters, homogeneity, pH, viscosity, adhesion and spreadability. Results: Serum preparations of weet star fruit leaf extract (Averrhoa carambola L.) in formula I, formula II and formula III have physical characteristics and stability that comply with SNI standards. Conclusion: The concentration of propylene glycol 25% in formula III shows the most stable serum stability properties compared to formula I and formula II